Cluster Analysis of the Expenditures for Environmental and Technological Innovations in Sustainable Development Policy Formation - TSENINA, Ekaterina Vladimirovna; DANKO, Tamara Petrovna; KISELEV, Vladimir Mikhailovich; CHAYKOVSKAYA, Lyubov Alexandrovna; EPSTEIN, Nikita Dmitrievich; RAUSKIENE, Ona; SEKERIN, Vladimir Dmitriyevich (Journal of Environmental Management and Tourism; Vol 13 No 1 (2022): JEMT, Volume XIII, Issue 1(57), Spring 2022DO - 10.14505/jemt.v13.1(57).06, 2022)
The major task of the present work is to identify the main problems of cluster analysis on environmental and technological innovations in the formation of regional sustainable development policy, as well as modeling the expenditures for technological and environmental innovations. The number of innovative enterprises increases rapidly, and they are developing at a rapid pace. Measures to reduce the impact on the environment, such as improving technological equipment, recycling waste, implementing technologies aimed at preserving natural resources, creating new types of products with long service life and the possibility of recycling, employing advanced purification technologies, etc. will require in the vast majority of cases not only financial expenditures but the implementation of innovative solutions. The authors are intended to study out and optimize this work and improve the research framework.